Environmentally Friendly Refining of Diamond-Molecules via the Growth of Large Single Crystals - Iwasa, Akio; Clay, Will A; Dahl, Jeremy E; Carlson, Robert M. K; Shen, Zhi-xun; Sasagawa, Takao (Crystal growth & design, 2010)
Using a home-made transparent two-zone furnace, single crystals of diamond molecules (or diamondoids) up to ∼1 cm3 were grown under real time observation using the vapor transport technique. This process proved to be an environmentally friendly means of refining diamond molecules. Optical measurements were performed to evaluate the purity of diamond molecules before and after the process, which demonstrated that even a trace amount of impurities in commercial samples was successfully removed by our method. The thus-obtained high-purity single crystals will accelerate fundamental and applied research on diamond molecules in the solid state, especially in the field of optoelectronics.